A 3-MicroRNA Signature Identified From Serum Predicts Clinical Outcome of the Locally Advanced Gastric Cancer - Chen, Shangxiang; Lao, Jiawen; Geng, Qirong; Zhang, Ji; Wu, Aiwen; Xu, Dazhi (Frontiers in Oncology, 2020)
Current staging systems are inadequate for evaluating the prognosis of patients with locally advanced gastric cancer (LAGC, stage II–III). Therefore, we developed a serum microRNA signature to facilitate individualized management of these patients. Using microarray analysis, we analyzed 12 serum specimens based on different prognoses (good survival group, n=7; poor survival group, n=5). We identified and confirmed differential expression of these miRNAs using qRT-PCR of serum from 51 patients with LAGC. A three miRNA-based classifier was established as a training set by Cox proportional hazard regression and risk-score analysis. We validated the prognostic accuracy of this model in an internal validation cohort (Sun Yat-Sen University Cancer Center, SYSUCC validation cohort, n=50) and an external independent cohort (Beijing Cancer Hospital, BJCH cohort, n=67). Three miRNAs were found to be associated with survival of LAGC (P<0.01 for miR-132, P=0.011 for miR-1826 and P<0.01 for miR-548a-3p). A three-miRNA signature was developed for the training set, and a significant difference was found between the survival of low-risk and high-risk score patients (P<0.01). The combination of the miRNA signature and TNM stage exhibited superior discrimination. Consistent results were obtained by further validation of the internal set and the BJCH set, which confirmed the predictive value of the model. We built an easy-to-use prognostic signature using three serum miRNAs as markers. Our miRNA signature may improve postoperative risk stratification and serve as a complement to the TNM staging system.